2016
DOI: 10.1186/s13068-016-0594-y
|View full text |Cite
|
Sign up to set email alerts
|

Lytic polysaccharide monooxygenases from Myceliophthora thermophila C1 differ in substrate preference and reducing agent specificity

Abstract: BackgroundLytic polysaccharide monooxgygenases (LPMOs) are known to boost the hydrolytic breakdown of lignocellulosic biomass, especially cellulose, due to their oxidative mechanism. For their activity, LPMOs require an electron donor for reducing the divalent copper cofactor. LPMO activities are mainly investigated with ascorbic acid as a reducing agent, but little is known about the effect of plant-derived reducing agents on LPMOs activity.ResultsHere, we show that three LPMOs from the fungus Myceliophthora … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
136
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 141 publications
(146 citation statements)
references
References 49 publications
(117 reference statements)
9
136
0
1
Order By: Relevance
“…It displays activity only on polysaccharides containing (1–4)-linked glucose units (cellulose, mixed linkages beta-glucans, glucomannans and xyloglucan). However, this enzyme does not cleave plant xylans as it is the case for the AA9 LPMO from Myceliophthora thermophila which is so far the only AA9 LPMO able to cleave xylan only when complexed to cellulose29. Phosphoric acid swollen cellulose (PASC) is one of the most common substrates used to monitor cellulase activity.…”
Section: Resultsmentioning
confidence: 99%
“…It displays activity only on polysaccharides containing (1–4)-linked glucose units (cellulose, mixed linkages beta-glucans, glucomannans and xyloglucan). However, this enzyme does not cleave plant xylans as it is the case for the AA9 LPMO from Myceliophthora thermophila which is so far the only AA9 LPMO able to cleave xylan only when complexed to cellulose29. Phosphoric acid swollen cellulose (PASC) is one of the most common substrates used to monitor cellulase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous results have shown that reducing agents with a 1,2-benzenediol or 1,2,3-benzenetriol moiety gave the highest release of non-oxidized and C1-oxidized gluco-oligosaccharides from regenerated amorphous cellulose (RAC) incubated with three Mt LPMOs compared to the incubation with compounds comprising only a single hydroxyl group [13]. Hence, in the current research we hypothesized that Mt LPMO activity can benefit from enzymes which have hydroxylating capacity, such as polyphenol oxidases (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2. The 21 different phenolic compounds used were classified into three groups and further divided into subgroups, as previously described [13]. In short, group I represents compounds comprising one hydroxyl group, group II compounds comprising a 1,2-benzenediol moiety, and group III compounds comprising a 1,2,3-benzenetriol moiety (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations